Systems Biology Analysis of the Effect and Mechanism of Qi-Jing-Sheng-Bai Granule on Leucopenia in Mice - Tian, Saisai; Huang, Pengli; Gu, Yu; Yang, Jian; Wu, Ran; Zhao, Jing; Liu, Ai-Jun; Zhang, Weidong (Frontiers in Pharmacology, 2019)
Qi-Jing-Sheng-Bai granule (QJSB) is a new developed traditional Chinese medicine (TCM) formula. In clinical, it has been used for the treatment of leucopenia. However, the therapeutic mechanism needs further solid investigation. In present study, we first tested the effect of QJSB on leucopenia mice induced by cyclophosphamide with administration of QJSB to leucopenia mice for 8 days. Our experiments showed that QJSB significantly increased the number of peripheral white blood cells, platelets and nucleated bone marrow cells. Meanwhile it markedly enhanced the cell viability and promoted the colony formation of bone marrow mononuclear cells. It also reversed the serum cytokines IL-6 and G-CSF disorders. Then, based on the data of transcriptomics derived from the bone marrow and metabonomic data from plasma, we integrated transcriptomics-based network pharmacology and metabolomics technologies to investigate the mode of action of QJSB. We found that QJSB regulates a series of biological processes such as hematopoietic cell lineage, homeostasis of number of cells, lymphocyte differentiation, metabolic processes (including lipid, amino acid and nucleotide metabolism), B cell receptor signaling pathway, T cell activation, and NOD-like receptor signaling pathway. In conclusion, QJSB exerts protective effect against leucopenia in mice probably through accelerating cell proliferation and differentiation, regulating metabolism response pathways and modulating immunologic function at system level. The multi-omics approach might achieve a complementary and verified view for the comprehensive evaluation of therapeutic effects and complex mechanisms of QJSB.